2017
DOI: 10.12716/1001.11.03.07
|View full text |Cite
|
Sign up to set email alerts
|

Criteria of Accidental Damage by Ships Anchors of Subsea Gas Pipeline in the Gda?sk Bay Area

Abstract: This paper discusses issues of the accidental anchor damage to offshore subsea pipeline as one of the most significant threat to underwater infrastructure. The density of vessel traffic over the pipeline between platform Baltic Beta and Wladyslawowo power plant has been analyzed. In order to determine the most common damages associated with heavy ship traffic, the authors used the risk model for underwater infrastructure. For this purpose ships anchor equipment has been categorized and as the results the crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although vessels that move across a pipeline route usually know the exact location of the pipeline to avoid anchoring in that location, anchors might be dropped during emergencies or due to technical failures. Based on the results of the research conducted by [4], it was possible to determine the ships that pose threats to pipelines. The research on a pipeline subjected to a dragged anchor by [10] showed that strain-based criteria provide the optimum result for a dent in a pipeline.…”
Section: Literature Studymentioning
confidence: 99%
“…Although vessels that move across a pipeline route usually know the exact location of the pipeline to avoid anchoring in that location, anchors might be dropped during emergencies or due to technical failures. Based on the results of the research conducted by [4], it was possible to determine the ships that pose threats to pipelines. The research on a pipeline subjected to a dragged anchor by [10] showed that strain-based criteria provide the optimum result for a dent in a pipeline.…”
Section: Literature Studymentioning
confidence: 99%